2011
DOI: 10.1002/ajmg.a.33446
|View full text |Cite
|
Sign up to set email alerts
|

Clinical phenotypes of a juvenile sibling pair carrying the fragile X premutation

Abstract: Individuals with alleles containing 55–200 CGG repeats in the fragile X mental retardation (FMR1) gene are premutation carriers. The premutation allele has been shown to lead to a number of types of clinical involvement, including shyness, anxiety, social deficits, attention deficit hyperactivity disorder (ADHD) and executive function deficits. Some of these problems could be due to mild deficits of the fragile X protein (FMRP) and a possible developmental effect of the elevated FMR1 mRNA observed in carriers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…In a case series of three boys and two girls with the premutation, ages 3 to 10, four had autism and one met criteria for ASD [19]. Basuta et al [20] described two siblings with the premutation (7 year old girl and 8 year old boy) both of whom had social anxiety and obsessive-compulsive symptoms, although the boy had more behavioral problems (attention deficits and hyperactivity). In a more heterogeneous group of 7 male and 43 female carriers ages 5-80, 14% of men and 5% of women met the Autism Diagnostic Observation Schedule-Generic criteria for ASD [21].…”
Section: Psychiatric Manifestations In Young Premutation Carriersmentioning
confidence: 99%
“…In a case series of three boys and two girls with the premutation, ages 3 to 10, four had autism and one met criteria for ASD [19]. Basuta et al [20] described two siblings with the premutation (7 year old girl and 8 year old boy) both of whom had social anxiety and obsessive-compulsive symptoms, although the boy had more behavioral problems (attention deficits and hyperactivity). In a more heterogeneous group of 7 male and 43 female carriers ages 5-80, 14% of men and 5% of women met the Autism Diagnostic Observation Schedule-Generic criteria for ASD [21].…”
Section: Psychiatric Manifestations In Young Premutation Carriersmentioning
confidence: 99%
“…In an early cohort study, daughters of carrier fathers, blinded to their father’s carrier status, reported more frequent behaviors related to adult ADHD [16]. This was followed by several case studies reporting ADHD behaviors in child carriers, such as difficulty focusing and sitting still in class [8,12,17] and a case-control study observing increased rates of ADHD in probands compared to non-probands and non-carriers [10]. Additional systematic studies have found a higher prevalence of adult ADHD in carriers compared to non-carriers [18].…”
Section: Neurodevelopmental Disorders In Carriersmentioning
confidence: 99%
“…While initially thought to be asymptomatic, carriers of a “pre-mutation” range repeat of 55–200 CGGs have a distinct clinical and molecular phenotype (Hagerman et al, 2001). Specifically, FXTAS patients acquire a progressive neurodegenerative disorder characterized by action tremor, gait difficulties, neuropsychiatric symptoms, peripheral neuropathy and dementia after the age of 50 (Hagerman et al, 2001; Basuta et al, 2011). …”
Section: Rna Dominant Neurological Disordersmentioning
confidence: 99%